THE EFFECT OF SAFETY PERCEPTION OF THE POLICE IN THE CITY OF DIYARBAKIR ON JOB SATISFACTION - Donmez, Mustafa (European Scientific Journal, ESJ, 2014)
Job satisfaction and the factors which influence the job satisfaction level of employees has been a popular subject among scholars. The aim of this study is to reveal if the safety perception of police officers and their families affects their job satisfaction levels in the city of Diyarbakir or not. Some other factors such as work environment, coworkers, supervisor support and demographics were used as control variables. Data for this study came from an employee satisfaction survey conducted among the personnel of the Diyarbakir Police Department (DPD), Turkey. Using Bivariate Correlation and Multivariate Regression analyses, it was found that perception of safety is a significant predictor of job satisfaction. More superficially, perception of own safety has an effect as strong as supervisor support, and the perception of family members’ safety has an effect almost three times as strong as supervisor support and perception of own safety.